Possibilities and limitations of research methods of the social structure in the Roman Iron Age in Poland - Gryzińska-Sawicka, Natalia (Folia Praehistorica Posnaniensia, 2015)
The question of structure of prehistoric communities constitutes an interesting, yet challenging research problem. Most often it is analyzed from the perspective of the equipment of individuals buried it cemeteries. Researchers dealing with the Roman period, largely base their studies on the qualitative and quantitative diversity of funerary material, assume that the richly furnished graves belonged to rich people (elites), and poorly equipped – respectively – to the poor. They take into account the present value of materials of which objects were made (gold, silver), even though they may not have been as significant as they are today. A major problem in the study of social structure turns out to be the poorly preserved bone material which often prevents anthropologists from determining sex and age of the deceased. The solution could be found in the study of fossil DNA, able to answer questions about the possible existence of kinship and family sectors in the cemeteries. What is more, the study of stable isotopes of oxygen, nitrogen and carbon, although not without limitations, can support archeology in finding answers to questions if diet could be related to social status (or dependent on sex, age, wealth, etc.). Finally, in the study of social structure, the research on divisions arising from labor and its distribution according to sex is also used. In the studies of social structure it is crucial to realize that burial is an intentional action, which is influenced by the aspirations of family members of the deceased, grief, emotions related to death, and even current “fashion”. Therefore, asking questions about the social structure and using methods which are to help obtain the answers, what we really ask about is the attitude of the living towards the deceased and death itself, as well as their own idea of the afterlife.